Effect of the Solvents Content on the Mechanical Response and Compactability of Asphalt Mixtures Fabricated Using Castilla’s Paving-Heavy Crude Oils (2020)
The paving-heavy crude oils (PHCO) are natural cut-back asphalts composed by a high content of asphalt cement and a portion of solvents. These materials have been used in Colombia since the 90’s to improve low volume traffic roads. The existence of solvents in the PHCO allows mixing it with the aggregates in cold conditions. Then, before compaction, these asphalt mixtures require a curing process (i.e., process of partial loss of solvents from the PHCO) to ensure its proper performance. However, at present there is no consensus on the loss of solvents to specify for the curing process of mixtures fabricated with PHCO. Given this situation, this study assesses the effect of the partial content of solvents on both the mechanical response and compactability of asphalt mixtures produced using PHCO from the Castilla’s oil field (CA); a material extensively used in the East region of Colombia. The study included conducting and analyzing conventional characterization tests of the mixture constituent materials, surface free energy testing on both mastics and the aggregate, mix design, and characterization of both mechanical response and compactability of the mixtures fabricated using the CA and a control asphalt. Corresponding results led to identify and quantify a progressive improvement in both the adhesion quality of the mastic-aggregate interfaces and the mechanical response of the asphalt mixture as a function of the reduction of the solvents. These results suggest the convenience of compacting the asphalt mixtures fabricated using the CA after allowing a loss of 50% of the solvents obtained from the CA via atmospheric distillation at 360°C.